PEMBINAAN DAN KINERJA GURU SEKOLAH MENENGAH ATAS NEGERI (SMAN) - Ermita Ermita; Anisah Anisah (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
This study aimed to obtain information about the performance of teachers and development of teachers by principals and relationship development of teachers by principals with teacher’s performance. The .hypothesis proposed in this study is “ there is significant relationship between the development of teacher by the principal and teacher’s performance of Public Senior Hight School in Bukittinggi City”. The population is 271 teachers and sample 152 were taken with Proporstional Stratified Random Sampling technique. Data collected by questionnaire that have tested the validity and reliability. Data analysis used Produch Moment correlation techniques with SPSS version 12.0 in 2007. The results showed that: (a) Performance of teacher is good (83.08% of the ideal score), (b) Development of teachers by principals is quite well (79.33% of the ideal score), (c) there is no significant relationship between teacher’s performance and development of teacher by principals at SMAN Bukittinggi.